THE ROLE OF THE AL-ITTIHAAD MADRASAH FORUM (FORMAT) ON QUALITY OF RELIGIOUS LEARNING IN MADRASAH DINIYAH AL-ITTIHAAD 2 PASIR LOR, KARANGLEWAS DISTRICT, BANYUMAS REGENCY - Nurfuadi Nurfuadi; Alivia Apriliyanti; Attabik Attabik; Rahman Afandi (International Journal of Social Science, 2022)
Globalization continues to have an impact on the social and cultural growth of Muslims in Indonesia in general, as well as Islamic education in particular in this millennial era, difficulties or moral problems involving the morals or character of the younger generation are the beginnings that often occur and we often face in society. They are more involved in gadgets and neglect to learn religious information from an early age. Thus, the existence of education such as Madrasah Diniyah is so important for the future of the younger generation in the context of improving the nation. Therefore, a forum or forum was formed to facilitate diniyah madrasas to improve performance, strategies, and the quality of religious learning by establishing a FORMAT or al-ittihaad madrasa forum. The research was conducted at Madrasah Diniyah Al-Ittihaad 2 Pasir Lor, Karanglewas District, Banyumas Regency using descriptive qualitative research. Observation, interview, documentation, and triangulation approach were used to collect information. The findings of the research conducted at Madrasah Diniyah Al-Ittihaad 2 Pasir Lor, Karanglewas District, Banyumas Regency regarding the Role of the Al-Ittihaad Madrasah Forum (FORMAT) on the Quality of Religious Learning, namely: 1) Al-Ittihaad Madrasah Forum (FORMAT) has attempted to develop its role to improve the quality of religious learning, namely by making curriculum regulations, learning entry hours, and rules. 2) The Al-Ittihaad Madrasah Forum has improved its performance, namely by developing programs or performance in improving the quality of religious learning with the existence of subject teacher associations and teacher meetings every month.